Analisis Tingkat Kematangan Keamanan Informasi Menggunakan Indeks KAMI pada Tiyuh Pulung Kencana - Khristina Henny R; M. Said Hasibuan (Journal of Digital Literacy and Volunteering, 2024)
Everyone must adapt quickly if they don't want to be left behind due to very rapid and significant technological developments. All institutions in Indonesia must also apply information technology to expedite and make their activities more effective and fulfill their duties and functions in implementing work programs. For this reason, the role of information security is very important to maintain the confidentiality, integrity and availability of information for the public and service interests. Based on the conditions described above, it is important to carry out a SID (Village Information System) assessment to determine the maturity and completeness of data security. Tiyuh Pulung Kencana Village in Tulang Bawang Tengah District, West Tulang Bawang Regency is the object of this research. This village or Tiyuh is one of the villages that has implemented SID effectively in the implementation of the Lampung Province Smart Village Program. The Information Security Index (KAMI) is used in Tiyuh Pulung Kencana, Tulang Bawang Tengah District, West Tulang Bawang Regency, to assess the completeness and maturity of the information security system. Document analysis and interviews with related parties are the qualitative methods used. The results of the KAMI index research show that Tiyuh Pulung Kencana relies heavily on electronic systems, but steps to protect information are still just starting (only in the initial stages). Therefore, Tiyuh Pulung Kencana must improve its information security practices by creating policies and procedures that comply with IT/IS standards and resource readiness.